2022
DOI: 10.2196/preprints.37480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Durability of the Treatment Effects of an 8-Week Self-administered Home-Based Virtual Reality Program for Chronic Low Back Pain: Follow-up Study of a Randomized Clinical Trial (Preprint)

Abstract: BACKGROUND We previously reported the efficacy of an 8-week home-based therapeutic immersive virtual reality (VR) program in a double-blind randomized placebo-controlled study. Community-based adults with self-reported chronic low back pain were randomized 1:1 to receive either (1) a 56-day immersive therapeutic pain relief skills VR program (EaseVRx) or (2) a 56-day sham VR program. Immediate posttreatment results revealed the superiority of therapeutic VR over sham VR for reducing pai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These differences from prior studies may be related to the fact that two of the five studies were pilot studies with very small numbers of participants and that three of the five studies provided only 4 weeks of intervention. Similarly, a double-blind randomized controlled trial study reported that giving patients who are living with low back pain a virtual reality intervention for 8 weeks had no meaningful impact on their level of self-efficacy (Garcia et al, 2021). Given that a prior study that employed interventions like yoga, physical therapy, and education found that self-efficacy had improved after 12 weeks, it is essential to conduct additional research with larger sample sizes and provide interventions for a sufficient period of time.…”
Section: Areas Needing Improvement -Self-efficacy and Mental Healthmentioning
confidence: 99%
“…These differences from prior studies may be related to the fact that two of the five studies were pilot studies with very small numbers of participants and that three of the five studies provided only 4 weeks of intervention. Similarly, a double-blind randomized controlled trial study reported that giving patients who are living with low back pain a virtual reality intervention for 8 weeks had no meaningful impact on their level of self-efficacy (Garcia et al, 2021). Given that a prior study that employed interventions like yoga, physical therapy, and education found that self-efficacy had improved after 12 weeks, it is essential to conduct additional research with larger sample sizes and provide interventions for a sufficient period of time.…”
Section: Areas Needing Improvement -Self-efficacy and Mental Healthmentioning
confidence: 99%